Analisis Daya Dukung Lahan Pertanian Tanaman Pangan Daerah Aliran Sungai Cibaliung, Provinsi Banten - Nurlaila Mubarokah; Latief Mahir Rachman; Suria Darma Tarigan (Institut Pertanian Bogor, 2020)
Analysis of carrying capacity of agricultural land for food crops is very important to do to determine the extent of the ability of agricultural land in supporting the fulfillment of the food needs of the population in an area. One problem in the Cibaliung watershed is the low ability of land to meet food needs so that residents cannot meet their needs independently. This study aims to determine the level of carrying capacity of agricultural food crops in meeting the food needs of the community in the Cibaliung River Basin (DAS) of Banten Province. Spatially, this study covered 2 regencies consisting of 15 districts within the scope of the Cibaliung watershed. The data used were secondary data taken from the Central Statistics Agency and the Agriculture and Animal Husbandry Office of Pandeglang and Lebak Regencies. The results showed that overall based on 4-year data (for the period of 2013‒2016) the carrying capacity of the Cibaliung watershed agricultural land as a whole was still low. In addition, the optimal number of populations that is able to be supported by the available food needs is still smaller than the total population recorded in each district in the Cibaliung watershed. This shows that the Cibaliung watershed area has not been able to be self-sufficient in food and has not been able to provide a decent life for its residents. Therefore, certain efforts need to be made to increase the carrying capacity of food agricultural land in this area, for example by suppressing the population and improving the quality of agricultural land resources through efforts to conserve agriculture and diversify food crop species. Keywords: agricultural land, carrying capacity, Cibaliung watershed